Viral antigens elicit augmented immune responses in primary Sjögren's syndrome. (30th October 2019) - Björk, Albin; Thorlacius, Gudny Ella; Mofors, Johannes; Richardsdotter Andersson, Elina; Ivanchenko, Margarita; Tingström, Joanna; James, Tojo; Brokstad, Karl A; Cox, Rebecca J; Jonsson, Roland; Kvarnström, Marika; Wahren-Herlenius, Marie
Abstract: Objectives: Infections have been suggested in the pathogenesis of primary SS (pSS). Systematic studies of immune responses to microbial antigens in vivo may be performed during vaccination. In the present study, we therefore longitudinally followed patients with pSS and controls during split-virion influenza vaccination to identify pSS-specific cellular, transcriptomic and serological responses. Methods: Patients without treatment (pSSUntr, n = 17), on hydroxychloroquine-treatment (pSSHCQ, n = 8), and healthy controls ( n = 16) were included. Antibody titres were determined by ELISA. Plasma proteins were measured by proximity extension assay. Monocyte gene expression was assessed by Nanostring. Routine laboratory tests were performed and clinical disease symptoms were registered by questionnaires. Results: pSSUntr developed higher vaccine-specific IgG titres compared with controls. Notably, anti-Ro52 autoantibody titres increased in pSSUntr but remained unchanged in pSSHCQ . No changes in disease symptoms including EULAR Sjögren's Syndrome Patient Reported Index score were registered. Twenty-four hours after vaccination, the leucocyte count in pSSUntr decreased, with a concomitant increase of CCL7 in plasma. Transcriptomic analysis in monocytes revealed differential vaccination-related expression of the NEMO/IKBKG gene, and its higher induced expression in pSSUntr associated with higher serological vaccine responses. Moreover, titres of vaccine-specific antibodies were associated with higher vaccination-induced NF-κB signalling and higher steady-state IFN signatures in monocytes, and with the levels of several plasma proteins with soluble PD-1 displaying the strongest association. Conclusion: We observed augmented innate and adaptive immune responses in pSS following viral antigen exposure suggesting an underlying hyper-responsiveness to immune challenges, supporting a role for infections driving the immunopathology and acting as environmental risk factor for pSS.